Do Disordered Eating Behaviours Have Long‐term Health‐related Consequences? - Kärkkäinen, Ulla; Mustelin, Linda; Raevuori, Anu; Kaprio, Jaakko; Keski‐Rahkonen, Anna (European eating disorders review, 2018)
Objective Long‐term health‐related consequences of disordered eating behaviours of young adults remain poorly understood. We examined whether disordered eating behaviours in mid‐20s are associated with physical and mental health 10 years later. Methods Women (n = 2631) and men (n = 2394) from a population‐based FinnTwin16 cohort were assessed using three subscales of the Eating Disorder Inventory‐2 at age 24. Self‐rated health, body mass index (BMI), waist circumference and psychological distress were assessed at age 24 and reassessed 10 years later. Results In crude models, disordered eating behaviours at age 24 were associated cross‐sectionally and prospectively with poor self‐rated health, higher BMI, larger waist circumference and psychological distress in both sexes. In models adjusted for baseline BMI and potential confounders, disordered eating behaviours predicted increased psychological distress in both sexes and poor self‐rated health in men. Conclusions Among young adults, disordered eating behaviours are associated with long‐term health‐related consequences, particularly psychological distress. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.